Molecular characterization of onion cultivars using microsatellite markers - Santos, Carlos Antonio Fernandes; Oliveira, Valter Rodrigues; Rodrigues, Marciene Amorim; Ribeiro, Hugo Leonardo Coelho (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to establish allelic patterns and to estimate genetic distances based on the SSR marker in 44 onion cultivars adapted to Brazil's tropical and subtropical growing conditions. An UPGMA dendrogram generated from the distance matrix of the Jaccard's coefficient, based on 40 alleles of 13 SSR loci, was used for visualizing genetic similarities. Total DNA was extracted according to the CTAB 2x protocol, and the PCR products were analyzed in 6% denaturing polyacrylamide gels and stained with silver nitrate. The number of base pairs was estimated by the inverse mobility method, based on regression of products of known size. The heterozygosity mean was 0.58 for all SSR loci. The 40 alleles of the 13 SSR loci were enough to distinguish all 44 onion cultivars. The highest number of common alleles was observed between Yellow Granex and Henry's Special PRR cultivars, and the lowest was observed between the Baia Periforme Super Precoce and Excel cultivars. The seven main groups of onion cultivars identified in the dendrogram were in agreement with the known genetic genealogy and with the agronomic type of the analyzed cultivars. The selected SSR loci are adequate for breeding programs and for protection of the cultivars of the species.